The Impact of Iron Overload in Patients with Acute Leukemia and Myelodysplastic Syndrome on Hepatic and Endocrine functions - Yassin, Mohamed A; Soliman, Ashraf; De Sanctis, Vincenzo; Hmissi, Saloua M; Abdulla, Mohammad AJ; Ekeibed, Yeslem; Ismail, Omer; Nashwan, Abdulqadir; Soliman, Dina; Almusharaf, Mohammed; Hussein, Redwa (Acta Biomedica Atenei Parmensis, 2018)
Patients with hematologic malignancies undergoing chemotherapy and requiring blood transfusion usually have an elevated serum ferritin. These findings have led to the suggestion that iron overload is common and may have deleterious effects in these patients. However, the relationship between serum ferritin and parenchymal iron overload in such patients is unknown. Therefore, we measured the liver iron content (LIC) by the FerriScan® method and investigated the liver function and some endocrine tests in 27 patients with acute leukemia (AL) or myelodysplastic syndromes (MDS). Using FerriScan® method, the normal mean LIC levels are: 4.3 ± 2.9 mg Fe/g dry weight (d.w.). In our patients, the mean serum ferritin level was 1965 ± 2428 ng/mL. In our patients, the mean total iron in the blood received by them was 7177 ± 5009 mg. In 6 out of 27 patients LIC was > 7 mg Fe/g d.w. and in 11/27 serum ferritin was > 1000 ng/ml. Measuring fasting blood glucose revealed 3/27 with diabetes mellitus and 4/27 with impaired fasting glucose (IFG). All patients had normal serum concentrations of calcium, parathormone (PTH), free thyroxine (FT4) and thyrotropin (TSH). Four patients had elevated serum alanine transferase (ALT). LIC was correlated significantly with ferritin level (r = 0.5666; P < 0.001) and the cumulative amount of iron in the transfused blood (r = 0.523; P